Addressing emotions in police selection and initial training: a European study - Moura, R. C.; Ramalho, N. C. (European Police Science and Research Bulletin, 2017)
Police officers have a strong need to control their personal emotions. Research that is focused on emotions is scarce but greatly needed regarding core institutional practices such as police selection and initial training. The purpose of this exploratory study is to uncover the extent to which police selection and training comprehends and addresses emotional issues across Europe. We examined European police forces via CEPOL, surveying the selection and initial training of career police personnel. Data were collected at country level with cross validation to ensure institutional representativeness. Data analysis made use of the MCA technique complemented by hierarchical clustering to identify patterns and emerging typologies. Transcripts from open-response questions concerning future trends in police selection and training were analysed for content. Findings show differing axes for official and officer selection practices and initial training, as well as dissimilar training hours in psychological subjects. No discernible pattern emerged for either career regarding selection dimensions or psychology subjects in initial courses. These findings rule out a strategic alignment between selection and training and do not allow one to foresee a common policy across countries and careers. An organisational research framework must emerge in order to tackle these issues.